2019
DOI: 10.1080/15538362.2019.1640167
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Market Participation among Smallholder Mango Producers in Assosa Zone of Benishangul Gumuz Region in Ethiopia

Abstract: Commercial transformation of smallholder agriculture entails production decisions based on market signals and significant participation in output markets. Consequently, this research attempts to contribute to the understanding of smallholder commercialization of mango production and analyzing factors determining the extent of smallholders' participation in output market. The study was based on the cross-sectional data collected from 150 sample households which were randomly selected from 6 rural kebeles. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A variety of research-utilizing household data have sought to explain the factors that influence smallholder decisions regarding investing in livestock markets (Hagos et al, 2019;Kyaw et al, 2018;Musemwa et al, 2010;Nwafor et al, 2020). A literature review shows contradictory proof of factors impacting the marketing of livestock markets, such as environmental, political, human, and institutional influences.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of research-utilizing household data have sought to explain the factors that influence smallholder decisions regarding investing in livestock markets (Hagos et al, 2019;Kyaw et al, 2018;Musemwa et al, 2010;Nwafor et al, 2020). A literature review shows contradictory proof of factors impacting the marketing of livestock markets, such as environmental, political, human, and institutional influences.…”
Section: Introductionmentioning
confidence: 99%
“…According to Ethiopia Fresh Fruits Market update report, production of mango increased by 45% from 2013/14 to 2017/18. However, considering these substantial quantities of mango fruit, the processing industry in Ethiopia is very weak (Hagos et al, 2019). In most situations, vendors and retailers buy the mango fruits from fruit collectors and from the people with the fruit tree at their home and transport them to urban markets where they sell them to other vendors, and to customers and some of the fruits exported to some countries.…”
Section: Introductionmentioning
confidence: 99%
“…Gebrehiwot et al (2018) reported that total land holding of the household, family size, the volume of vegetables produced and marketed, usage of irrigation technologies, interaction with extension agents, and access to market information and vegetable marketing significantly improve the livelihoods of smallholder producers. Similarly, other studies (Hagos et al, 2020;Hao et al, 2018;Megerssa et al, 2020;Ola & Menapace, 2020) were conducted on the different factors affecting the marketing/commercialization of agricultural products by using different methods of data analysis. However, none of the above studies incorporated the endogeneity of the market participation decision process, and selection due to both observable and unobservable characteristics.…”
Section: Introductionmentioning
confidence: 99%